2018
DOI: 10.1039/c7ra13464a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic colloidal pastes for surface-enhanced Raman spectroscopy (SERS) of historical felt-tip pens

Abstract: Surface-enhanced Raman spectroscopy (SERS) has been identified as a suitable technique for the analysis of colorants in works of art. Herein, the application of SERS to the identification of dye compositions in historical felt-tip pens is reported, which is of paramount importance for the development of appropriate conservation protocols for historical drawings. In this study, three pens (pink, green, and blue colors) belonging to the film director Federico Fellini were analyzed. SERS measurements were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This could be due to the fact that slightly different blues were compared (Caran D'Ache 555 against Fellini Caran D'Ache 100) or that the composition of the blue Caran D'Ache used by Fellini in 1960s has changed with time. The comparison of results obtained with benchtop Raman instrumentation previously carried out in our group showed that comparable results were obtained under the two experimental conditions (benchtop illumination wavelength 514 nm, resolution 3–5 cm −1 , spot size 2–5 μm, laser power <2 mW, handheld illumination wavelength 514 nm, 10–12 cm −1 , resolution, 1 mm spot size, laser power 50 mW). In blue Fellini, additional traces of rhodamine were detected by benchtop Raman illumination.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This could be due to the fact that slightly different blues were compared (Caran D'Ache 555 against Fellini Caran D'Ache 100) or that the composition of the blue Caran D'Ache used by Fellini in 1960s has changed with time. The comparison of results obtained with benchtop Raman instrumentation previously carried out in our group showed that comparable results were obtained under the two experimental conditions (benchtop illumination wavelength 514 nm, resolution 3–5 cm −1 , spot size 2–5 μm, laser power <2 mW, handheld illumination wavelength 514 nm, 10–12 cm −1 , resolution, 1 mm spot size, laser power 50 mW). In blue Fellini, additional traces of rhodamine were detected by benchtop Raman illumination.…”
Section: Resultssupporting
confidence: 65%
“…SERS was also used by our group and others for the identification of dye content in ballpoint pens . Recently, SERS was also used in combination with other analytical techniques for the identification of dyes in commercial felt‐tip pens and used to identify colorants in colored inks used by artists such as Lucio Fontana and Federico Fellini . As an increasing number of modern artworks are already entering a state of high degradation, the inherent noninvasiveness, high sensitivity, and efficient quenching of interfering fluorescence signals could make SERS the analytical technique of choice to support the development of long‐term conservation methods for modern artworks.…”
Section: Introductionmentioning
confidence: 99%
“…From previous work carried out in our group, it is known that green inks are often constituted by a mixture of blue and yellow dyes and that blue phthalocyanine Solvent Blue 38 pigment (C.I. 74180) is used in BIC pen formulations . Therefore, presence of CuPh Blue 38 was hypothesized.…”
Section: Resultsmentioning
confidence: 99%
“…74180) is used in BIC pen formulations. [27] Therefore, presence of CuPh Blue 38 was hypothesized. Clearer indication of Blue 38 occurrence in green pens was obtained by SERS analysis at 532 nm (see Figure S3) where Medium, Crystal and Medium Crystal green pens showed diagnostic bands at 1,541, 1,453, 1,341, and 712 cm −1 .…”
Section: Name Colormentioning
confidence: 99%
See 1 more Smart Citation